Using Simulation-Based Learning with Standardized Patients (SP) in an Implicit Bias Mitigation Clinician Training Program - Jennifer Tjia; Michele Pugnaire; Joanne Calista; Ethan Eisdorfer; Janet Hale; Jill Terrien; Olga Valdman; Stacy Potts; Maria Garcia; Majid Yazdani; Geraldine Puerto; Miriam Okero; et al. (Journal of Medical Education and Curricular Development, 2023)
Objectives To describe the development and refinement of an implicit bias recognition and management training program for clinical trainees. Methods In the context of an NIH-funded clinical trial to address healthcare disparities in hypertension management, research and education faculty at an academic medical center used a participatory action research approach to engage local community members to develop and refine a “knowledge, awareness, and skill-building” bias recognition and mitigation program. The program targeted medical residents and Doctor of Nursing Practice students. The content of the two-session training included: didactics about healthcare disparities, racism and implicit bias; implicit association test (IAT) administration to raise awareness of personal implicit bias; skill building for bias-mitigating communication; and case scenarios for skill practice in simulation-based encounters with standardized patients (SPs) from the local community. Results The initial trial year enrolled n  =  65 interprofessional participants. Community partners and SPs who engaged throughout the design and implementation process reported overall positive experiences, but SPs expressed need for greater faculty support during in-person debriefings following simulation encounters to balance power dynamics. Initial year trainee participants reported discomfort with intensive sequencing of in-person didactics, IATs, and SP simulations in each of the two training sessions. In response, authors refined the training program to separate didactic sessions from IAT administration and SP simulations, and to increase safe space, and trainee and SP empowerment. The final program includes more interactive discussions focused on identity, race and ethnicity, and strategies to address local health system challenges related to structural racism. Conclusion It is possible to develop and implement a bias awareness and mitigation skills training program that uses simulation-based learning with SPs, and to engage with local community members to tailor the content to address the experience of local patient populations. Further research is needed to measure the success and impact of replicating this approach elsewhere.